(3GdeMce aj GddZIs - (3Ydj Hf ESeGYjd, GdeYQha H` GHf SjOg, CHh GdMSf,J (B458 (3g` s
(3ChdgG (B:s
(3jHOC CKfGA GdcdGe Yf GdcGa hGdSjf hGdQGA Hbhdg (B: (3hGdcSQ GdcSQ hGdaJM CYdi GdLRA ef GdYVh hbjd gh GdYVh GdhGaQ s
(3BNQgG (B:s
(3jfJgi HGfJgGA GdcdGe Yf GdLje hGddGe hGdhGh Hbhdg (B: (3hCfTO jYbhH (B: (3hHGOQ GdYaQ Jhe GdOhdLG hbO GKdL GdXHi ai cfGSg s
(3GdfSNI HgG MhGTs
(3LRA jHOC CKfGA GdcdGe Ydi GdcGa hGdSjf hGdQGA HChdgG JedjcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B263 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B36s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GddZIs